Aerobic degradation of crude oil by microorganisms in soils from four geographic regions of China. Issue 1 (December 2017) - Liu, Qinglong; Tang, Jingchun; Gao, Kai; Gurav, Ranjit; Giesy, John
Abstract A microcosm experiment was conducted for 112 d by spiking petroleum hydrocarbons into soils from four regions of China. Molecular analyses of soils from microcosms revealed changes in taxonomic diversity and oil catabolic genes of microbial communities. Degradation of total petroleum hydrocarbons (TPHs) in Sand from the Bohai Sea (SS) and Northeast China (NE) exhibited greater microbial mineralization than those of the Dagang Oilfield (DG) and Xiamen (XM). High-throughput sequencing and denaturing gradient gel electrophoresis (DGGE) profiles demonstrated an obvious reconstruction of the bacterial community in all soils. The dominant phylum of the XM with clay soil texture wasFirmicutes instead ofProteobacteria in others (DG, SS, and NE) with silty or sandy soil texture. Abundances of alkane monooxygenase geneAlkB increased by 10- to 1000-fold, relative to initial values, and were positively correlated with rates of degradation of TPHs and n-alkanes C13-C30. Abundances of naphthalene dioxygenase geneNah were positively correlated with degradation of naphthalene and total tricyclic PAHs. Redundancy analysis (RDA) showed that abiotic process derived from geographical heterogeneity was the primary effect on bioremediation of soils contaminated with oil. The optimization of abiotic and biotic factors should be the focus of future bioremediation of oil contaminated soil.